2014
DOI: 10.1111/1467-9817.12025
|View full text |Cite
|
Sign up to set email alerts
|

The association between academic self‐beliefs and reading achievement among children at risk of reading failure

Abstract: This paper investigates whether children's academic self-beliefs are associated with reading achievement and whether the relationship is modified by gender and/or age. Data were collected from children at risk of reading failure, that is, emergent readers (6-to 8-year-olds) in socioeconomically disadvantaged areas reading at a level below the population mean. The authors' own measure of attitude to reading and perceived competence was used. The study found a significant positive association between attitude to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…AR also had greater explanatory power when predicting reading achievement than AS and PCS. This finding lends support to the hypothesis that self-beliefs matched to specific academic domains will better predict performance in that domain than self-beliefs that are more global in scope (Fives et al, 2014;Hansford & Hattie, 1982;Logan & Johnston, 2009;Pullmann & Allik, 2008;Valentine et al, 2004). The explanatory power of AR also compared well with the sub-scales of the PiersHarris multi-domain measure of self-concept.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…AR also had greater explanatory power when predicting reading achievement than AS and PCS. This finding lends support to the hypothesis that self-beliefs matched to specific academic domains will better predict performance in that domain than self-beliefs that are more global in scope (Fives et al, 2014;Hansford & Hattie, 1982;Logan & Johnston, 2009;Pullmann & Allik, 2008;Valentine et al, 2004). The explanatory power of AR also compared well with the sub-scales of the PiersHarris multi-domain measure of self-concept.…”
Section: Discussionsupporting
confidence: 63%
“…The findings show that, although girls did not score significantly higher than boys for reading achievement, nonetheless, as other studies have reported Fives et al, 2014;Kelley & Decker, 2009) girls had more positive self-beliefs than boys. The findings also show the interaction between AR and reading achievement was significantly different for boys and girls, as the positive association was stronger among girls than boys.…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…Asking children to self‐report in regard to their attitudes and perceived competence raises a concern about reporter bias. However, results from data collected using this measure have shown statistically significant positive associations between attitude to reading and reading achievement (Fives et al ., in press).…”
Section: Methodsmentioning
confidence: 99%
“…Once a school has labeled a student as "at risk" or "intellectually slow," it sets a student down a problematic path. There exists a significant and growing amount of research (Cox & Guthrie, 2001;Fives et al, 2014;Hall, 2005;Lim, Bong, & Woo, 2015;Logan, Medford, & Hughes, 2011;J. K. Smith, Smith, Gilmore, & Jameson, 2012) that correlates reading attitudes and engagement to the amount of reading children do, factors which directly contribute to future reading achievement.…”
Section: Cultural Difference and Cultural Sensitivity: Multiculturalimentioning
confidence: 99%